2005
DOI: 10.1073/pnas.0509181102
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the chemical and dynamic properties of cardiac troponin T cause discrete cardiomyopathies in transgenic mice

Abstract: Cardiac troponin T (cTnT) is a central component of the regulatory thin filament. Mutations in cTnT have been linked to severe forms of familial hypertrophic cardiomyopathy. A mutational ''hotspot'' that leads to distinct clinical phenotypes has been identified at codon 92. Although the basic functional and structural roles of cTnT in modulating contractility are relatively well understood, the mechanisms that link point mutations in cTnT to the development of this complex cardiomyopathy are unknown. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 39 publications
11
84
1
Order By: Relevance
“…trophic phenotype (mild) from the cellular phenotype (moderate to severe) in iTAC mice was striking; not only does this finding support several recent studies in which the pathogenic cardiovascular response was separated from myocellular growth, it extends our understanding of the central role of the nature of the inciting stimulus (10)(11)(12). Thus, these results definitively show that while the duration of the discrete pathogenic stimulus may dictate the magnitude of ventricular hypertrophy, chronicity is not sufficient to cause hypertrophic heart disease - the nature of the inciting stimulus must be pathogenic.…”
Section: Figuresupporting
confidence: 73%
See 1 more Smart Citation
“…trophic phenotype (mild) from the cellular phenotype (moderate to severe) in iTAC mice was striking; not only does this finding support several recent studies in which the pathogenic cardiovascular response was separated from myocellular growth, it extends our understanding of the central role of the nature of the inciting stimulus (10)(11)(12). Thus, these results definitively show that while the duration of the discrete pathogenic stimulus may dictate the magnitude of ventricular hypertrophy, chronicity is not sufficient to cause hypertrophic heart disease - the nature of the inciting stimulus must be pathogenic.…”
Section: Figuresupporting
confidence: 73%
“…Activation of myocellular remodeling via alterations in biomechanical stretch (mechanotransduction) plays an important role in many cardiomyopathies including those caused by postinfarction remodeling and mutations in cytoskeletal and sarcomeric proteins (17). Indeed, animal models of both dilated and hypertrophic cardiomyopathies (representing intrinsic mechanical stress) have demonstrated a similar dissociation between myocellular pathology and growth, as seen in the iTAC mice (12,18). Thus, both extrinsic and intrinsic pathologic stimuli may activate similar myocellular responses involving both G protein-dependent and -independent signaling pathways.…”
Section: A Potentially Broader Paradigm To Spur New Approaches To An mentioning
confidence: 85%
“…3) to study both structural and dynamic changes as a result of mutation. As has been shown in previous studies, mutations cause changes to both local and long-range interactions (17,18,20,21). The long-range effects are difficult to discern when such complex systems are not studied in atomistic detail.…”
Section: Resultsmentioning
confidence: 93%
“…MD uses protein structure data to predict the motion of atoms within molecules on picosecond time scales. In one case, MD has been used to predict motion of a critical region of the troponin T (TnT) molecule in the presence of FHC-linked mutations R92W and R92L [19]. Simulations showed that both mutations tended to destabilize helical structures in the protein, increasing flexibility of the molecule relative to the wild-type sequence.…”
Section: Sarcomeric Proteinsmentioning
confidence: 99%
“…In such a case, the initial challenge to relate a specific mutation to the type of cardiac remodelling becomes one of relating the mutation to Ca 2þ sensitivity. Knowing the amino acid sequence of normal and mutant proteins should provide important clues, and some progress is being made in this regard through the use of molecular dynamics (MD) simulations (see Ertz-Berger et al [19] and Lorenz & Holmes [20]). MD uses protein structure data to predict the motion of atoms within molecules on picosecond time scales.…”
Section: Sarcomeric Proteinsmentioning
confidence: 99%